Cramer’s Rule applied to flexible systems of linear equations - Justino, Júlia (2014)
Systems of linear equations, called flexible systems, with coefficients having uncertainties of type o (.) or O (.) are studied. In some cases an exact solution may not exist but a general theorem that guarantees the existence of an admissible solution, in terms of inclusion, is resented. This admissible solution is produced by Cramer’s Rule; depending on the size of the uncertainties appearing in the matrix of coefficients and in the constant term vector some adaptations may be needed.